The Importance of Student-Teacher Matching: A Multidimensional Value-Added Approach - Ahn, Tom; Aucejo, Esteban M.; James, Jonathan (The Review of Economics and Statistics, 2025)
We propose a framework for value-added models that flexibly characterizes heterogeneous teacher productivity based on multidimensional student characteristics. We show that teacher effectiveness heavily depends on the specific attributes of their students. For example, the difference in value-added between well-matched and poorlymatched students for the average teacher is approximately 0.1 standard deviations in test scores. Notably, these matching effects are particularly pronounced among lowachieving students. In language arts, the standard deviation in teacher value-added is one-third larger for low-achieving students compared to high-achieving students.